(untitled) (Perner’s Contacts, 2011)
This paper is about projects of University of Žilina (especially projects which are realized at Air Transport Department in cooperation with Flight Training Organization (FTO) – Air School of the University of Zilina) and are supported and co-financed by structural founds of EU. At this moment the Air Transport Department deals with three projects: Implementation of science-research knowledge to the Air Transport -ITMS 26220220010, Centre of excellence for Air Transport -ITMS 26220120065, Q Brokerage centre of Air Transport for Transfer of Technology and knowledge into Transport and Transport Infrastructure- ITMS 26220220156.